Toward a Sustainable Sense of Self in Teaching and Teacher Education: Sustainable Happiness and Well-Being Through Mindfulness - Kyte, Darlene (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
This paper examines the effects of mindfulness practice through pranayama, hatha yoga, and meditation on practicing teachers in an inner city school to determine if practices of this nature could contribute to sustainable sense of self, sustainable happiness, and well-being for practicing teachers and pre-service teachers. Furthermore, mindfulness practice is discussed in the context of new pedagogies that are contributing to the transformation of teachers, students, and education. This inquiry has demonstrated that this process not only offers the practitioner serenity, awareness, peace, and well-being: but the benefits of the practice move far beyond the personal environment of those practicing teachers and into the classroom and school community providing opportunities for transformation; growing sustainable happiness and well-being.